Harmonic Characteristic Analysis of Magnetically Saturation Controlled Reactor - Tian Ming Xing; Yuan Dong Sheng; Yan Hong (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
As the magnetically saturation controlled reactor’s (MSCR) operation is based on the saturation characteristic of the core, so its harmonic characteristic should be valued. According to the structural characteristic and working principle, the mathematical model of MSCR is derived. And the harmonic components of physical quantities such as current, voltage and magnetic field parameters are analyzed by function characteristic analysis. Then, it concludes that MSCR’s working current is an odd harmonic function, containing fundamental and odd harmonic components; controlling current and voltage are even harmonic functions, containing DC and even harmonic components; the core flux linkage, flux, magnetic field intensity and magnetic field density are just containing DC and fundamental components. At last, a simulation model for MSCR is fabricated with MATLAB/Simulink, the simulation results show that the paper’s analysis and conclusions are accurate. So, this paper can provide a reference to further analysis and proposition of new harmonic suppression methods of MSCR. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.2276